Stereoselective Synthesis of 3, 4‐Dihydroxylated Prolines and Prolinols Starting from L‐Tartaric Acid. (31st October 2013) - Oba, M.; Koguchi, S.; Nishiyama, K.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>